Assessing Patient Progress in Psychological Therapy Through Feedback in Supervision: the MeMOS* Randomized Controlled Trial (*Measuring and Monitoring clinical Outcomes in Supervision: MeMOS). Issue 3 (7th February 2017) - Davidson, Kate M.; Rankin, Michelle L.; Begley, Amelie; Lloyd, Suzanne; Barry, Sarah J.E.; McSkimming, Paula; Bell, Lisa; Allan, Carole; Osborne, Morag; Ralston, George; Bienkowski, Geraldine; Mellor-Clark, John; et al.
Abstract : Background: Psychological therapy services are often required to demonstrate their effectiveness and are implementing systematic monitoring of patient progress. A system for measuring patient progress might usefully 'inform supervision' and help patients who are not progressing in therapy.Aims : To examine if continuous monitoring of patient progress through the supervision process was more effective in improving patient outcomes compared with giving feedback to therapists alone in routine NHS psychological therapy.Method : Using a stepped wedge randomized controlled design, continuous feedback on patient progress during therapy was given either to the therapist and supervisor to be discussed in clinical supervison (MeMOS condition) or only given to the therapist (S-Sup condition). If a patient failed to progress in the MeMOS condition, an alert was triggered and sent to both the therapist and supervisor. Outcome measures were completed at beginning of therapy, end of therapy and at 6-month follow-up and session-by-session ratings.Results: No differences in clinical outcomes of patients were found between MeMOS and S-Sup conditions. Patients in the MeMOS condition were rated as improving less, and more ill. They received fewer therapy sessions.Conclusions : Most patients failed to improve in therapy at some point. Patients' recovery was not affected by feeding back outcomes into the supervision process. Therapists rated patients in the S-Sup condition as improving more and being less ill than patients in MeMOS. Those patients in MeMOS had more complex problems.